Prediction of CO and NOx Abatement in Catalytic Converter of a Compressed Natural Gas Vehicle (CNGV) Cold-Start Engine - Abdullah, Luqman Chuah; Jolius, Gimbun; Fakhru'l-Razi, A.; Sahari, Barkawi; Thomas, S. Y. Choong (Nova Science Publishers, 2011)
Simulation and modelling of cold-start engine exhaust behaviour at catalytic converter is a difficult task as it involves complicated heat transfer processes and chemical reactions. This work presents a Computational Fluid Dynamics (CFD) calculation to predict the transient thermal and conversion characteristics of catalytic converters during the light-off operation. The numerical solutions was realised using a species transport modelling in a first and second order differencing scheme. The effects of temperature on conversion of NOx to N2 and CO to CO2 are numerically evaluated and all results are in an excellent agreement with the published measurement. The calculated light-off temperature of catalytic converter is in the range of 530 and 600 K which was in the range of the data that reported in the literature. Results obtained from the simulation have demonstrated that CFD is capable of modelling the catalytic converter cold-start behaviour.